Didymodon cordatus Jur. (Pottiaceae), new to the moss flora of China - Zhao, Dong-Ping; Bai, Xue-Liang; Wang, Jian-Nan; Liu, Yang (Bangladesh Journal of Plant Taxonomy, 2013)
Not available. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17402 Bangladesh J. Plant Taxon. 20(2): 259-261, 2013